2023
DOI: 10.1007/s11356-023-31314-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of green finance and local regulations on industrial green innovation efficiency in China

YiHan Xia,
LuYi Luo,
KaiWen Ji
et al.

Abstract: When the incentive mechanism of green finance fails to fully promote green technology innovation in industrial enterprises, local government environmental regulations become an important tool in correcting this market failure. However, due to the “follow the cost” hypothesis, the moderating effect of the local government environmental regulation is heterogeneous. In order to explore the impact mechanism of green finance development on the efficiency of green technology innovation in industrial enterprises, spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Xu and Zhu ( 9 ) showed that China’s overall green governance index and green financial policies resulted in a significant decrease in environmental pollution. Xia et al ( 10 ) presented evidence that green finance significantly cultivates green innovation and benefits the promotion of green innovation both in local jurisdictions and adjacent provinces. Guo et al ( 11 ) contended that the effect of executing new energy demonstration cities is more significant in central and western regions, as well as in smaller and mid-sized urban areas, particularly regarding the emission reduction effect.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Xu and Zhu ( 9 ) showed that China’s overall green governance index and green financial policies resulted in a significant decrease in environmental pollution. Xia et al ( 10 ) presented evidence that green finance significantly cultivates green innovation and benefits the promotion of green innovation both in local jurisdictions and adjacent provinces. Guo et al ( 11 ) contended that the effect of executing new energy demonstration cities is more significant in central and western regions, as well as in smaller and mid-sized urban areas, particularly regarding the emission reduction effect.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Research based on the Yangtze River Economic Belt has shown a high degree of coupling and coordination between green finance and industrial green development [29], which provides indirect evidence for green finance to improve urban haze. Furthermore, in terms of promoting environmental protection through green finance, existing research mainly posits that green finance helps to control environmental pollution through the optimized allocation of financial resources, signal transmission [30], industrial structure optimization and upgrading [31], environmental regulation [32], green total factor productivity [33,34], and enterprise green innovation [35].…”
Section: Introductionmentioning
confidence: 99%